Design and performance of a dedicated coherent X‐ray scanning diffraction instrument at beamline NanoMAX of MAX IV. (16th March 2022) - Carbone, Dina; Kalbfleisch, Sebastian; Johansson, Ulf; Björling, Alexander; Kahnt, Maik; Sala, Simone; Stankevic, Tomas; Rodriguez-Fernandez, Angel; Bring, Björn; Matej, Zdenek; Bell, Paul; Erb, David; et al.
Abstract : The design and the basic performances of the diffraction endstation of the NanoMAX beamline of MAX IV Laboratory in Lund are presented. Designed to perform scanning diffraction, the endstation is adapted to single‐particle imaging as well as scanning fluorescence microscopy, tomography, and 2D and 3D ptychography in forward and Bragg geometries, using high‐flux nanofocused (coherent) X‐ray beams in the energy range between 5 and 28 keV. Abstract : The diffraction endstation of the NanoMAX beamline is designed to provide high‐flux coherent X‐ray nano‐beams for experiments requiring many degrees of freedom for sample and detector. The endstation is equipped with high‐efficiency Kirkpatrick–Baez mirror focusing optics and a two‐circle goniometer supporting a positioning and scanning device, designed to carry a compact sample environment. A robot is used as a detector arm. The endstation, in continued development, has been in user operation since summer 2017.